MANAJEMEN ALOKASI DANA DESA (ADD) DI DESA TEGALWERU, KECAMATAN DAU, KABUPATEN MALANG - Alifiulahtin Utaminingsih; Irma Fitriana Ulfah; Fathur Rahman; Andi Setiawan (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
Law No. 6 of 2014 provides fresh air for the village government ie one with the allocation of village income derived from the state budget or called the Village Fund (DDS). The priority of DDS use is to finance village-level programs and local activities in the field of development and empowerment. Total DDS received by Tegalweru Village in 2016 amounted to Rp 610,416,000.00 and in 2017 increased to Rp.777.771.000,00. This DDS becomes the largest income for Tegalweru Village compared to ADD and sharing of local taxes and levies. The use of DDS in Tegalweru Village is in line with development priorities and empowerment, but not yet fully accommodated. The areas of development that have been done in 2016 are the development of educational infrastructure facilities, roads, village offices, and community and social development. In 2016 there is no development of production facilities and energy development and environmental sustainability. By 2017, roads, bridges, health facilities, electric power and settlement have been built. In addition to development, both in 2016 and 2017 have also been carried out the empowerment of health and institutional capacity building.